Nicotine effects on rat seizures susceptibility and hippocampal neuronal degeneration - Riljak, Vladimír; Maresova, Dana; Pokorny, Jaroslav (Neuro endocrinology letters, 2010)
OBJECTIVES: Nicotine is a widely used drug of abuse exerting number of effects on the central nervous system. The study was aimed at the effects of nicotine in various doses on the excitability of cerebral cortex and - by using the methods of histochemistry - to identify possible signs of neuronal degeneration after nicotine administration. METHODS: Cortical afterdischarges were elicited by repeated stimulation of the right sensorimotor cortex. The duration of evoked ADs was monitored in animals treated with nicotine (0.75 or 1.0mg/kg) and in animals treated with saline. Methods of histochemistry (Fluoro-Jade B and bis-benzimide) were used to detect possible neuronal degeneration in hippocampus or in cerebral cortex. RESULTS: No Fluoro-Jade B positive cells were found in hippocampi of control animals, or animals treated with nicotine. ADs length was significantly influenced by administration of nicotine. CONCLUSION: Nicotine in 0.75 or 1.0 mg/kg dose leads to the decrease in ADs duration, influences the seizure susceptibility, and doesn't cause any detectable neuronal damage.
Keywords: Neurons; Dose-Response Relationship, Drug; záchvaty; Electrophysiology; vztah mezi dávkou a účinkem léčiva; nikotinoví agonisté; Random Allocation; Rats; implantované elektrody; evokované potenciály; motorické korové centrum; degenerace nervu; hipokampus; Evoked Potentials; náchylnost k nemoci; Disease Models, Animal; Rats, Wistar; Electrodes, Implanted; elektrofyziologie; injekce intraperitoneální; Seizures; Nerve Degeneration; krysa rodu Rattus; Motor Cortex; nikotin; Injections, Intraperitoneal; modely nemocí na zvířatech; mozková kůra; zvířata; Cerebral Cortex; náhodné rozdělení; neurony; Disease Susceptibility; potkani Wistar; Nicotinic Agonists; Nicotine; Hippocampus; Animals